MicroRNA and Putative Target Discoveries in Chrysanthemum Polyploidy Breeding - Fengjiao Zhang; Jingya Zhao; Sujuan Xu; Weimin Fang; Fadi Chen; Nianjun Teng (International Journal of Genomics)
MicroRNAs (miRNAs), around 22 nucleotides (nt) in length, are a class of endogenous and noncoding RNA molecule that play an essential role in plant development, either by suppressing the transcription of target genes at a transcriptional level or inhibiting translation at a posttranscriptional level. To understand the roles of miRNAs and their target genes in chrysanthemum polyploidy breeding, three sRNA libraries of normal and abnormal embryos after hybridization were performed by RNA-Seq. As a result, a total of 170 miRNAs were identified and there are 41 special miRNAs in cross of paternal chromosome doubling, such as miR169b, miR440, and miR528-5p. miR164c and miR159a were highly expressed in a normal embryo at 18 days after pollination, suggesting the regulatory role at the late stage of embryonic development. miR172c was only detected in the normal embryo at 18 days after pollination, which means that miR172c mainly mediates gene expression in postembryonic development and these genes may promote embryo maturation. Other miRNAs, including miR414, miR2661, and miR5021, may regulate the genes participated in pathways of auxin response and energy metabolism; then they regulate the complex embryonic development together.